The Climate Stigmatization of the Global Oil and Gas Industry: Response Strategies - Alexey Bereznoy (Foresight and STI Governance)
One of the most recent trends in the global economy is the stigmatization of the global oil and gas industry, i.e., the sharply negative public perception of the industry as a whole, and of its key players in particular. These processes, directly related to the aggravation of the climate-related issues, have already become a source of substantial problems for major industry players. In recent years, public opinion regarding major international oil and gas corporations has changed markedly, at least in most Western countries. Global industry leaders (the so-called supermajors) are increasingly perceived as an existential threat to humanity, laying on them the main responsibility for global warming. Faced with the challenges of the industry-level public ostracism (industry stigma), these companies have been the first to develop a set of responses. This paper attempts to take a fresh look at the supermajors’ climate strategies for responding to the industry stigma. Looking through the prism of the stigma management concept helps one identify the reasons behind the changes in global oil and gas corporations’ relevant strategies in the course of their evolution, and understand the logic behind the different approaches to the green transformation employed by European and US supermajors.